2013
DOI: 10.5851/kosfa.2013.33.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanopowdered Peanut Sprouts on Physicochemical and Sensory Properties of Milk

Abstract: A study was conducted to examine the physicochemical and sensory properties of milk supplemented with nanopowdered peanut sprouts (NPPS) at different concentrations (1, 3, 5, 7, and 9%, w/v) during the storage at 4 o C for 16 d. The size of NPPS ranged from 300-350 nm as observed by the particle size analyzer. The pH values of all samples ranged from 6.8 to 6.6 during the storage of 16 d. In color, the L* value of milk samples were not remarkably influenced by NPPS supplementation, whereas the b* and a* value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…It has the potential to enhance foods in various ways, such as increasing the bioavailability of nanonutrients in foods. The increase of bioavailability of calcium through nanosizing has been recently reported in several studies (Park et al, 2008;Hilty et al, 2011;Seo et al, 2011;Ahn et al, 2013). We recently observed in an (unpublished) animal study that the bioavailability of nanopowdered oyster shell (NPOS) and zinc-activated NPOS (Zn-NPOS) increased to 29.14 and 60.76%, respectively, over that of powdered oyster shell (POS; 10%).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…It has the potential to enhance foods in various ways, such as increasing the bioavailability of nanonutrients in foods. The increase of bioavailability of calcium through nanosizing has been recently reported in several studies (Park et al, 2008;Hilty et al, 2011;Seo et al, 2011;Ahn et al, 2013). We recently observed in an (unpublished) animal study that the bioavailability of nanopowdered oyster shell (NPOS) and zinc-activated NPOS (Zn-NPOS) increased to 29.14 and 60.76%, respectively, over that of powdered oyster shell (POS; 10%).…”
Section: Introductionmentioning
confidence: 84%
“…However, NPOS-and Zn-NPOS-supplemented milks were not significantly affected (P > 0.05). The dispersible nanochitosan (Seo et al, 2011) and nanopowdered peanut sprouts (Ahn et al, 2013) were also reported to not affect milk in terms of appearance, flavor, or taste. Based on the data obtained in this study, we suggest that supplementing milk with NPOS and Zn-NPOS at concentrations 0.5 and 1.0% (vol/vol) would be acceptable to consumers.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Bioavailability enhancement through nanosizing has been recently reported in a number of studies, for example in milk supplemented with nanopowdered peanut sprouts (Ahn et al . ), yoghurt supplemented with nanochitosan (Seo et al . ) and milk supplemented with nanocalcium (Park et al .…”
Section: Introductionmentioning
confidence: 99%
“…Yogurt is an important fermented dairy products that contains all nutrients and probiotics which are consumed for many generations in various countries (Gobbetti et al 2004;Ahn et al 2012). Beneficial flora, such as the genera of Bifidobacterium or Lactobacillus, could inhibit the growth of pathogenic bacteria and decrease the level of carcinogenic This work was supported by the Jungwon University Research Grants.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the demand of yogurt, health beneficial yogurt should be focused and developed. In recent years, many different food ingredients including peanut spouts extract (Ahn et al 2012), yam (Hsu et al 2006), chitosan (Seo et al 2011), and ginseng (Lee et al 2013) have been formulated into yogurt formulations to improve the nutritional value.…”
Section: Introductionmentioning
confidence: 99%